Evolution of Physical Activity Surveillance, Policy, and Research in China: Insights From the Global Observatory for Physical Activity (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This study aimed to assess the trends and changes in physical activity (PA) surveillance, policy, and research in China over a decade (2015–2025), using data from the Global Observatory for Physical Activity (GoPA!) Country Card for China.Methods: We utilised data from the first (2015), second (2020), and third (2025) sets of the GoPA! Country Card for China, as well as data collected from public sources and in consultation with Chinese PA experts. This included indicators related to PA surveillance, national policies, research output, as well as demographic and socioeconomic factors. Descriptive statistics were used to summarise the data and identify patterns over time.Results: Between 2015 and 2025, China’s population grew from 1.36 billion to 1.41 billion, with urbanisation increasing from 59.2% to 63.9% (between 2020 and 2025). Life expectancy improved from 75 to 77.9 years, and the Human Development Index (HDI) rose from 0.69 to 0.79. The literacy rate remained high, reaching 97% in 2025.China’s overall PA prevalence increased from 76% in 2015 to 86% in 2020 but declined back to 76% in 2025. Meanwhile, the proportion of deaths in China that are attributable to non-communicable diseases (NCDs) rose from 86% in 2015 and 2020 to 88.5% in 2025. There was a decrease in deaths related to physical inactivity from 8.3 to 3.8%. Unlike in most countries, females are more active than males.China’s PA surveillance system has been consistently maintained, with the first survey conducted in 2000 and the latest in 2015. Standardised tools like the Global Physical Activity Questionnaire and the International Physical Activity Questionnaire were utilised to evaluate PA levels. National PA policies have evolved, introducing key initiatives such as the Healthy China 2030 plan and the National Fitness programme (2021–2025) between 2015 and 2025.Conclusion: Over the past decade, China has made significant progress in PA surveillance, policy, and research. However, the fluctuating prevalence of PA and the rising NCD mortality, potentially linked to population ageing and the COVID-19 pandemic, underscore the necessity for more effective PA promotion strategies and additional research.